التعسف في استعمال الحق في الأسرة بين الشريعة والقانون في أقليم كردستان العراق : دراسة تحليلية - أبو بكر، عمر خضر (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
The phenomenon of arbitrariness is one of the social and legal problems experienced by the human community and suffered by man throughout his life, and abuse in general relates to many aspects, including the abuse of public and private rights of man. This research focused on the phenomenon of abuse in the use of the right in family issues in the Kurdistan region of Iraq, especially My rights to divorce and custody, through Comparison between the provisions of Islamic law and the personal status law and its amendments in the Kurdistan region of Iraq. Based on the importance of the family and its leading position in the lives of societies and peoples, as it is seen as the home in which the rights of family members, young and old, are preserved; The Al-Manhal family is the source of love, serenity, mercy, strength, solidarity and cohesion, from which everyone draws. However, water does not always flow in its path. Rather, some problems and conflicts arise in the lives of families that have expanded and increased in prevalence in the current era, including the abuse of the right, which has disturbed the peace Family relations, and the occurrence of injustice and the derogation of the rights of some family members, intentionally or out of ignorance. Therefore, Islam legislated provisions and precautionary controls that protect individuals from the use of abuse against them.and then; The researcher touched on the detection of some abuses against the family, and the abuse of it and its rights, especially in the field of the dissolution of the marital bond and its psychological and physical effects, as in the right of custody, for example. for the family, the tenderness of parents; Damage is not limited to the family environment, but extends to society. The researcher concluded that the problem of abuse has transformed from a situation to a general phenomenon, and the many cases and cases before the courts in the Kurdistan region of Iraq bear witness to this. The researcher noted the discrepancy in the positions of Sharia and law in some aspects of divorce and custody, and accordingly; The researcher presented some solutions and proposals to limit the abuse of the right in the family, and avoid the threatening effects on the family and society. In line with the developments and requirements of modern life.